Composition, structure and properties of electroless deposited nickel – phosphorus – copper coatings - Tsybul’skaya, Ludmila S.; Perevoznikov, Sergey S.; Shendyukov, Vladislav S. (Journal of the Belarusian State University. Chemistry, 2019)
The nickel – phosphorus – copper functional coating was deposited on aluminum alloys substrate by chemical deposition method from malonateglycinate nickel plating solution. The chemical and phase coatings composition was studied by Xray fluorescence and Xray phase analyze. Thermally stimulated phase transitions in deposited Ni – P – Cu coating were detected by differential scanning calorimetry method. The annealing at 250 and 400 °С was shown to lead to the changes in coating structure involving the transition from amorphous to amorphouscrystalline at 250 °С and to crystalline at 400 °С with Ni and Ni3P1 –  δ  phases forming. Changes in the structure of Ni–P coating results in the increase of microhardness by 1.6–1.7 times and wear resistance by 3– 4 times. Annealing at 400 °С led to decreasing of corrosion stability of the coatings in 3.5 % sodium chloride solution. The optimum physical, mechanical and protective properties has the attained in the case of Ni – P – Cu coating annealed at 250 °C.
Keywords: nickel – phosphorus – copper coating; composition; structure; annealing; corrosion protection properties; microhardness; wear resistance